Technology Digital Resources Needs for Japanese Grammar Learning - Permatasari, Kun Makhsusy; Agustine, Irawati (International Journal of Educational Research & Social Sciences, 2024)
This study aims to determine the need for digital technology resources in Japanese grammar classes through student perceptions. The research method uses qualitative descriptions. This study was conducted at a private university in Jakarta in the even semester of 2023-2024. The participants involved were students who received Japanese grammar classes totalling 70 students. The data collection process used observation, interviews, and documents. Data analysis used the stages of data reduction, data presentation, and concluding. The findings concluded that there are four types of digital technology resources needed by students and the most interview answers were university websites (35.7%) and videos from YouTube (35.7%). Other types are websites for downloading books and learning websites from various educational institutions at home and abroad. Overall, it was found that the existence of digital technology resources has a positive impact on learning Japanese grammar. This is also supported by the ownership of smartphone